Literatur Review: Penggunaan Model Pembelajaran Problem Based Learning dengan Pendekatan STEM dalam Pembelajaran Fisika di Sekolah - Ima Ainur Rohmah; Zidan Afidah; Aisyah Ayu Nur Azizah Maharani; Niken Noviana Mahmudyah; Rif`ati Dina Handayani; Pramudya Dwi Aristya Putra (UNIVERSITAS INDRAPRASTA PGRI, 2023)
The PBL or Problem Based Learning learning model with the STEM approach can be used to enhance student learning activities. Because the learning process with the PBL learning model with the STEM approach is expected to improve students' critical thinking skills. This study uses the literature review method by collecting data from previous researchers. This study uses a literature review taken from 25 journals published in the last 5 years and indexed by Sinta or National Proceedings, namely Sinta 1 to Sinta 5. The results of this study indicate that students can improve their critical thinking skills and researchers use many samples from class X for their research, the physics material that is widely used by researchers is the physics of work and energy. While the constraints of the researchers are limited time and lack of time management, research conducted by researchers is carried out online as a result of being constrained by the internet network, requiring participation, courage and self-confidence of students. The results of this study are expected to help teachers apply the PBL learning model with the STEM approach in class.